PERAN POLA PENGASUHAN ORANGTUA TERHADAP SIKAP NASIONALISME REMAJA - Agoes Dariyo; R. Rahaditya (Provitae: Jurnal Psikologi Pendidikan, 2017)
Aim of this research is to know the differences of nationalism based on the parenting style. There are 121 adolescents involve in the research. Data collecting by questionarries such as parenting style and nationalism. Anova, regression and correlation are used to analysis the data. The result is, there are differences nationalism based on the parenting style (F = 3.236, p = . 043 < .05). There is correlation between authoritative parenting style and nationalism (r = .405(**), p = .000 < . 01). There is no correlation between authoritarian parenting style and nationalism (r = . 0,190, p = .810 > .05), and there is correlation between permissive parenting style and nationalism (r = . 377, P = . 0283 < .05). Beside, there is the role of authoritative parenting style on the nationalism (r2 = . 164, t = 4542, p= .000 < .01). Score r2 = . 164 means the contribution of authoritative parenting style on the nationalism is 16. 4 % and the other factors wich contribute on the nationalism is 83.6 %.Keywords: parenting style, nationalism, and adolescence.